2007
DOI: 10.2174/1874318807001010001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Propagation of Hepatitis E Virus in Experimentally Infected Swine

Abstract: HEV infections in human and pigs have been reported in many countries; however, the precise distribution and multiplication of this virus in the host remains poorly understood. In this study, we examined the distribution and multiplication of HEV genotype 3 in two piglets at the early phase of intravenous infection, and also examined the virus distribution in a naturally infected pig. We developed real-time RT-PCR to determine copy numbers of the HEV genome in the sera, feces and organs. HEV-RNA was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…It has been observed that swine HEV can be readily detected in sera and feces from pigs since 1 week after experimental injection of HEV [Meng et al, 1998;Halbur et al, 2001]. Viremia was shown to occur transiently, whereas virus particles were shed in feces of infected pigs for long duration at high viral load [Hagiwara et al, 2007]. In fact, when individual sera and feces of ten 2-month-old pigs were tested for HEV RNA, viremia was found in three pigs, whereas viral genome in feces was detected in seven samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that swine HEV can be readily detected in sera and feces from pigs since 1 week after experimental injection of HEV [Meng et al, 1998;Halbur et al, 2001]. Viremia was shown to occur transiently, whereas virus particles were shed in feces of infected pigs for long duration at high viral load [Hagiwara et al, 2007]. In fact, when individual sera and feces of ten 2-month-old pigs were tested for HEV RNA, viremia was found in three pigs, whereas viral genome in feces was detected in seven samples.…”
Section: Discussionmentioning
confidence: 99%
“…Horseradish peroxidase-labeled goat anti-swine IgG (Kirkegaard and Perry Laboratories, Inc., Gaithersburg, MD) at 1:10,000 dilution was added to detect swine-specific immunoglobulin. Pooled sera from experimentally infected pigs, a gift from Dr. Katsuro Hagiwara (Rakuno Gakuen University; Hokkaido, Japan) [Hagiwara et al, 2007], were used as a positive control for anti-HEV antibodies. Antibody titers were defined as Index-values calculated from OD values with following formula, Index-value ¼ (OD value of sample/ OD value of positive control) Â 100.…”
Section: Detection Of Anti-hev Igg Antibody By Elisamentioning
confidence: 99%
“…HEV was found present in the duodenum, jejunum, ileum, colon, caecum at copy numbers lower than 1000 RNA copies/g by PCR while blood titers were not determined [ 51 ]. Recently, a mean virus concentration of 3.3 × 10 3 genome copies/g was found in the intestine of 69 wild boar in central Italy [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, the homogenized samples were centrifuged at 8000 rpm for 5 min, and the supernatants were collected in sterile tubes. RNA from pig livers, experimentally infected with HEV, was used as a positive control, and non-HEV-infected healthy pigs were used as a negative control [22]. Viral RNA was extracted from fecal supernatants using a QIAamp Viral RNA extraction kit (QIAGEN, Hilden, Germany) according to the kit's protocol, and 50 mg from each liver tissue was lysed with 1 mL Trizol (Invitrogen, Carlsbad, CA, USA).…”
Section: Rna Extraction and Detection Of Hev Rna By Rt-pcrmentioning
confidence: 99%